Sexual victimization among University of Benin fresh female students: intervention implication (2016)
Sexual victimization against young girls and women has been extensively studied for decades however, little is known about the factors that predispose an individual to sexual victimization. This study therefore adopted a correlational survey design to examine the extent to which parent-child communication, peer pressure and media influence are associated with sexual victimization among fresh female students in the University of Benin, Nigeria. Six hundred fresh female students whose age ranged from 16 to 19 (x =SD=17.65) were drawn using simple sampling technique in three stages. They responded to four standardized self-report measures. Pearson Product Moment Correlation and regression statistics were used to analyze data at 0.05 level of significance. Result show that parent-child communication has negative relationship with sexual victimization, while peer pressure and media influence were positively associated with sexual victimization. The independent variables accounted for 39% of the total variance in the prediction of sexual victimization. In terms of magnitude peer- pressure made the most potent contribution while media usage made the least contribution. The need to empower parents with effective parent-child communication skills was emphasized among other recommendations.